An engaging pedagogy for an academic curriculum. Issue 2 (3rd April 2019) - Rata, Elizabeth; McPhail, Graham; Barrett, Brian
Abstract: The article discusses the link between a curriculum based on academic subjects derived from disciplinary knowledge and a progressive pedagogy that endeavours to engage students from all backgrounds with it. Section 1 describes the realist theory of knowledge which justifies the argument for this accommodation between curriculum and pedagogy. Section 2 explains how conceptual progression serves as an effective curriculum design strategy for supporting pedagogy. The final section discusses how concepts and studies from within the social realist tradition can be used to theorise an accommodation between curriculum and pedagogy that promotes cumulative knowledge building among students and teachers by being responsive to both the students and to the knowledge being taught in motivating ways.